IDENTIFIKASI PENERAPAN JALUR PEMANDU DI SLB A YAPTI MAKASSAR - Eko Bebi Yusuf Pratama (JURNAL ORTO DIDAKTIKA, 2023)
The focus of this study refers to the results of observations made by researchers at SLB A Yapti Makassar where researchers found accessibility facilities in the form of guideways in several rooms, especially in school corridors. However, the guide lines in the school have differences, one of which is the texture of the tiles used do not show embossed lines on the guide lines. This is different from the guiding paths that researchers have used in public places which have a raised line texture on the tiles.The purpose of this study is to find out how the implementation of the guide line at SLB A Yapti Makassar. This research uses a qualitative approach with a descriptive research type. Data collection techniques in this study used observation, interviews and documentation. This research is located at SLB A Yapti Makassar. The conclusions of this study are (1) the guiding paths in these schools are not up to standard. Where the guideline does not use guide tiles and warning tiles (Guiding Block). And (2) Students at the school can take advantage of the available guideline, even though the guideline is still very limited.